Meso‐Modified Cobalamins: Synthesis, Structure, and Properties. Issue 41 (27th June 2018) - Wierzba, Aleksandra J.; Wincenciuk, Aleksandra; Karczewski, Maksymilian; Vullev, Valentine I.; Gryko, Dorota
Abstract: Vitamin B12 and its derivatives present excellent paradigms for bioinspired catalysis. The inherent challenges for derivatizing cobalamins, such as vitamin B12, to incorporate them in supramolecular designs and materials, limit the range of their utility and applications. Herein, we present a synthetic approach toward derivatives of vitamin B12 possessing electron‐donating and ‐withdrawing substituents at the meso position (C10). Spectroscopic and cyclic voltammetry studies reveal that changes in the substitution pattern on the equatorial ligand have a significant impact on the electronic and optical properties of the cobalamin. These synthetic methods, therefore, provide invaluable routes not only for covalent linking to other structures, but also for attaining a wide range of functionalities for the derivatives of vitamin B12 . Abstract : Herein, we present a synthetic approach toward derivatives of vitamin B12 possessing electron‐donating and ‐withdrawing substituents at the meso position (C10). Spectroelectrochemical studies reveal that changes in the substitution pattern on the equatorial ligand have a significant impact on the electronic and optical properties of the cobalamin.